Enhancing the accreditation of Indonesian private universities through the integration of EduQual and accreditation standards of the BAN-PT - Mirandhi Pratiwi; Lien Herliani Kusumah (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2024)
Higher education institutions in Indonesia are currently facing significant challenges in maintaining public trust, requiring them to uphold autonomy, transparency, accountability, and continuously meet standards for quality assurance and improvement. This research aims to identify and address the unmet quality aspects in education to elevate the accreditation of private universities from C/Good to B/Very Good or even A/Excellent. By integrating the EduQual model with certification requirements from the Board of National Accreditation for Higher Education (Badan Akreditasi Nasional Perguruan Tinggi, BAN-PT), the research is supported by comprehensive studies of university accreditation reports, questionnaires, focus group discussions (FGD), and expert judgment through interviews and consultations. The data analysis employs gap analysis, importance-performance analysis, and quality function deployment. The study identified twenty-one priority improvement points to enhance accreditation, with six key improvements prioritized from the ninety indicators examined based on customer needs analysis. In the accreditation of private universities, the unmet aspects of education quality lie in the dimension of physical facilities, particularly human resources, as well as in the dimension of personal development, especially in the criteria for research and community service. The study recommends prioritizing investments in human resource development and strengthening research and community service initiatives, as these are critical areas where private universities fall short in meeting accreditation standards and fulfilling educational quality expectations.